2011
DOI: 10.1007/s11199-011-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Attachment and Television Viewing in Adolescents’ Sexual Socialization: Differential Associations Across Gender

Abstract: The present study explores whether gender and maternal attachment moderate the relationship between television viewing and adolescents' sexual and gender stereotypical attitudes. A quantitative survey was conducted among 1,026 Belgian adolescents in a targeted sample of nine schools (Mean age=16.3). Findings show that greater exposure to television among boys and lower maternal attachment among boys and girls is associated with more liberal and stereotypical sexual attitudes. While maternal attachment has a bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 73 publications
2
24
0
1
Order By: Relevance
“…It is noteworthy that we did not find a threeway interaction effect between pubertal status, the use of sexually explicit websites, and either gender or age on sexual initiation. Regarding gender, this finding is in contrast with the results from studies on the use of television (Vandenbosch & Eggermont, 2012) and sexually explicit media in general (Brown & L'Engle, 2009), but it is consistent with research on sexually explicit websites. Valkenburg (2008a, 2009a,b) have repeatedly reported no gender differences for the longitudinal relationship between using sexually explicit websites and adolescents' sexual development.…”
Section: Pubertal Status and Sexual Media Effectssupporting
confidence: 66%
See 1 more Smart Citation
“…It is noteworthy that we did not find a threeway interaction effect between pubertal status, the use of sexually explicit websites, and either gender or age on sexual initiation. Regarding gender, this finding is in contrast with the results from studies on the use of television (Vandenbosch & Eggermont, 2012) and sexually explicit media in general (Brown & L'Engle, 2009), but it is consistent with research on sexually explicit websites. Valkenburg (2008a, 2009a,b) have repeatedly reported no gender differences for the longitudinal relationship between using sexually explicit websites and adolescents' sexual development.…”
Section: Pubertal Status and Sexual Media Effectssupporting
confidence: 66%
“…The survey included questions on the control variables, pubertal status, sexual initiation, and the use of sexually explicit websites. The questions were based on instruments whose validity and reliability have been established in prior research involving English-and Dutch-speaking adolescents (Armsden & Greenberg, 1987;Eggermont, 2006;Peter & Valkenburg, 2008a;Peter & Valkenburg, 2008b;Stephenson, Hoyle, Palmgreen, & Slater, 2003;Vandenbosch & Eggermont, 2012). Instruments that had not yet been translated into Dutch were evaluated and approved by a panel of fellow researchers at the host university and pretested using a small sample of adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…They interpret this finding as evidence of the concept of mainstreaming, in that A c c e p t e d M a n u s c r i p t 8 television use helped the outlooks of those differing by religiosity to converge around shared support for same sex relationships. Other studies have identified important differences by respondents' gender in associations between overall TV viewing and holding gender stereotypes regarding sexual and romantic roles, in particular (Ter Bogt et al, 2010, Vandenbosch & Eggermont, 2012. colleagues (2016, 2017) provide the closest parallels to the study at hand.…”
Section: Television and Masculinity: General Patternsmentioning
confidence: 90%
“…Medyada sunulan cinsel içerikli yayınlar yukarıda da bahsedildiği gibi cinsellik açısından çeşitli kalıp yargılar barındırmaktadır (Ward ve Friedman, 2006). Dolayısıyla bu tür yayınlara maruz kalmak ergenlik dönemindeki bireylerin cinsellikle ilgili çeşitli kalıp yargılar geliştirmesine ve bu konudaki kalıp yargıları daha fazla benimsemesine neden olabilmektedir (Beem ve ark., 2015; Keastle, Harpern ve Vandenbosch ve Eggermont, 2012;Ward, 2002;Ward ve Friedman, 2006). Örneğin, bu konuda yürütülen bir çalışmada (Ward, 2002) daha yoğun ve ilgili bir biçimde televizyon izleyen gençlerin cinsellikle ilgili kalıp yargıları daha fazla benimsedikleri gösterilmiştir.…”
Section: B Cinsellik Ve Cinsiyete Ilişkin Tutum Ve Inanışlar üZerindunclassified